2019
DOI: 10.1242/dev.177659
|View full text |Cite
|
Sign up to set email alerts
|

Sall4 regulates neuromesodermal progenitors and their descendants during body elongation in mouse embryos

Abstract: Bi-potential neuromesodermal progenitors (NMPs) produce both neural and paraxial mesodermal progenitors in the trunk and tail during vertebrate body elongation. We show that Sall4, a pluripotency-related transcription factor gene, has multiple roles in regulating NMPs and their descendants in post-gastrulation mouse embryos. Sall4 deletion using TCre caused body/tail truncation, reminiscent of early depletion of NMPs, suggesting a role of Sall4 in NMP maintenance. This phenotype became significant at the time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 68 publications
4
53
0
Order By: Relevance
“…5' Hox genes are known to exhibit posterior prevalence via more anterior gene repression (Lewis, 1978;Zhu et al, 2017). Our data further suggested that Enh4 may be activated by NMp regulators such as sall4 and raraa (Gouti et al, 2017;Tahara et al, 2019) in NMp cells and repressed by high levels of foxd3 and other NC regulators, such as zic2b and klf7a, in NC cells ( fig. S3, S5 B-C).…”
Section: Distinct Foxd3 Regulatory Landscapes In the Cranial Nc And Tsupporting
confidence: 65%
“…5' Hox genes are known to exhibit posterior prevalence via more anterior gene repression (Lewis, 1978;Zhu et al, 2017). Our data further suggested that Enh4 may be activated by NMp regulators such as sall4 and raraa (Gouti et al, 2017;Tahara et al, 2019) in NMp cells and repressed by high levels of foxd3 and other NC regulators, such as zic2b and klf7a, in NC cells ( fig. S3, S5 B-C).…”
Section: Distinct Foxd3 Regulatory Landscapes In the Cranial Nc And Tsupporting
confidence: 65%
“…Interestingly, gene ontology (GO) analysis of ZFC4-regulated genes identified GO terms associated with neuronal differentiation, morphogenesis, gonad development and kidney development (Table S3), all of which are adversely affected in Sall4 knockout mice and embryos (Böhm et al, 2008; Sakaki-Yumoto et al, 2006; Tahara et al, 2019; Akiyama et al, 2015; Koshiba-Takeuchi et al, 2006; Chan et al, 2017; Hobbs et al, 2012; Xu et al, 2017; Yamaguchi et al, 2015; Warren et al, 2007). This suggests the possibility that SALL4 plays an essential role in the transition between self-renewing ESCs and the differentiated state by preferentially suppressing the expression of AT-rich developmental genes, thus preventing premature loss of pluripotency.…”
Section: Resultsmentioning
confidence: 99%
“…To identify novel AT-binding proteins, we utilized a DNA pulldown-mass spectrometry screen in mouse embryonic stem cells (ESCs) which are pluripotent and can be differentiated in culture. As a top hit we identified SALL4 which is a multi-zinc-finger protein that restrains differentiation of ESCs (Yuri et al, 2009; Miller et al, 2016) and participates in several physiological processes, including neuronal development (Böhm et al, 2008; Sakaki-Yumoto et al, 2006; Tahara et al, 2019), limb formation (Akiyama et al, 2015; Koshiba-Takeuchi et al, 2006) and gametogenesis (Chan et al, 2017; Hobbs et al, 2012; Xu et al, 2017; Yamaguchi et al, 2015). Deletion of the Sall4 gene leads to embryonic lethality shortly after implantation (Sakaki-Yumoto et al, 2006; Elling et al, 2006; Warren et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To identify novel AT-binding proteins, we utilized a DNA pull-down mass spectrometry screen in mouse embryonic stem cells (ESCs), which are pluripotent and can be differentiated in culture. As a top hit, we identified SALL4, which is a multi-zinc-finger protein that restrains differentiation of ESCs ( Yuri et al., 2009 ; Miller et al., 2016 ) and participates in several physiological processes, including neuronal development ( Böhm et al., 2008 ; Sakaki-Yumoto et al., 2006 ; Tahara et al., 2019 ), limb formation ( Akiyama et al., 2015 ; Koshiba-Takeuchi et al., 2006 ), and gametogenesis ( Chan et al., 2017 ; Hobbs et al., 2012 ; Xu et al., 2017 ; Yamaguchi et al., 2015 ). Deletion of the Sall4 gene leads to embryonic lethality shortly after implantation ( Sakaki-Yumoto et al., 2006 ; Elling et al., 2006 ; Warren et al., 2007 ).…”
Section: Introductionmentioning
confidence: 99%